2018
DOI: 10.1016/j.nmni.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium simiae pulmonary disease in Iran: systematic review and meta-analysis

Abstract: Mycobacterium simiae is one of the most common nontuberculous mycobacteria (NTM) microorganisms causing lung disease in many countries in the world. A reliable estimate of the extent of M. simiae pulmonary disease has not been well investigated in Iran. We systematically searched multiple databases to identify relative studies. Studies were excluded if they did not use the American Thoracic Society (ATS) and Infectious Diseases Society of America (IDSA) diagnostic criteria for NTM diseases. Data were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Based on the previous studies, 10 to 47% of the patients with NTM had true M. simiae infection [5,15,16]. We have recently indicated the clinical isolation of M. simiae by some studies in Iran, but the ecology behind this is not well understood [17]. We hypothesize that the high rate of M. simiae in Iran, may be due to the contamination of water supplies with this pathogen, a finding that was previously reported in studies conducted in Iran [18,19].…”
Section: Discussionmentioning
confidence: 60%
“…Based on the previous studies, 10 to 47% of the patients with NTM had true M. simiae infection [5,15,16]. We have recently indicated the clinical isolation of M. simiae by some studies in Iran, but the ecology behind this is not well understood [17]. We hypothesize that the high rate of M. simiae in Iran, may be due to the contamination of water supplies with this pathogen, a finding that was previously reported in studies conducted in Iran [18,19].…”
Section: Discussionmentioning
confidence: 60%
“…In Lebanon, M. simiae represents 30% to 65% of isolated NTM over the past two decades [4]. A recent meta-analysis from Iran found that the pooled national prevalence of M. simiae among NTM is 25% [16].…”
Section: What Are the Epidemiology And Regional Distribution Of M Simentioning
confidence: 99%
“…NTM infections are one of the important causes of death due to tuberculosis (TB) treatment failure [2]. Non-tuberculous mycobacteria which include about 200 known species are classified into two major groups, including slow-growing mycobacteria (SGM), and fast-growing mycobacteria (RGM), based on growth rate [1][2][3]. One of the most frequent NTM is Mycobacterium simiae (M. simiae) which has been recognized as an opportunistic pathogen and health concern in various areas throughout the world, including Iran [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Non-tuberculous mycobacteria which include about 200 known species are classified into two major groups, including slow-growing mycobacteria (SGM), and fast-growing mycobacteria (RGM), based on growth rate [1][2][3]. One of the most frequent NTM is Mycobacterium simiae (M. simiae) which has been recognized as an opportunistic pathogen and health concern in various areas throughout the world, including Iran [3,4]. M. simiae is a photochromogenic, slow-growing NTM that was first isolated from Cercopthecus aethiops and Macacus rhesus monkeys in 1965 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%